1998
DOI: 10.1128/mcb.18.6.3201
|View full text |Cite
|
Sign up to set email alerts
|

5′ Processing of tRNA Precursors Can Be Modulated by the Human La Antigen Phosphoprotein

Abstract: Eukaryotic precursor (pre)-tRNAs are processed at both ends prior to maturation. Pre-tRNAs and other nascent transcripts synthesized by RNA polymerase III are bound at their 3 ends at the sequence motif UUU OH [3 oligo(U)] by the La antigen, a conserved phosphoprotein whose role in RNA processing has been associated previously with 3-end maturation only. We show that in addition to its role in tRNA 3-end maturation, human La protein can also modulate 5 processing of pre-tRNAs. Both the La antigen's N-terminal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
129
0
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 108 publications
(138 citation statements)
references
References 46 publications
7
129
0
2
Order By: Relevance
“…La resides mostly within the nucleus where it is involved in the processing of RNA polymerase III transcripts (Fan et al, 1998;Intine et al, 2003) and acts as a retention factor for mature preexisting mRNAs (Brenet et al, 2005). La can shuttle between the nucleus and cytoplasm upon cellular stress (Baboonian et al, 1989;Bachmann et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…La resides mostly within the nucleus where it is involved in the processing of RNA polymerase III transcripts (Fan et al, 1998;Intine et al, 2003) and acts as a retention factor for mature preexisting mRNAs (Brenet et al, 2005). La can shuttle between the nucleus and cytoplasm upon cellular stress (Baboonian et al, 1989;Bachmann et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Unlike with La, the sequences/secondary structures of the vRNA required for its binding to TEP1 have not yet been determined. Interestingly, in addition to an RNA binding domain, TEP1 also contains a Walker A motif, which in La has been shown to interact with the 5Ј-ppp of pre-tRNAs (27). Because the vRNA is not capped and has a 5Ј-pppG, this motif may be another binding site for interaction with La and/or TEP1.…”
Section: Tep1 Vparp and Vrna Are Not Exclusivelymentioning
confidence: 99%
“…The concentration of La protein in the S100 extract of HeLa cells is calculated to be 50 nM (Fan et al, 1998). It would appear that binding of La protein to JEV RNA is physiologically plausible, and using a co-immunoprecipitation experiment, we demonstrated that the JEV genome did indeed interact with endogenous La in JEV-infected HEK293A cells.…”
Section: Discussionmentioning
confidence: 78%